Memories of the collective action of teachers’ networks in Latin America - Díaz Becerra, Lizeth Marcela (Praxis, 2024)
Teachers’ networks and collectives have been consolidated as spaces for self-management of contextualized pedagogical practices with a view to building hopeful projects for the country based on other ways of being a teacher and schooling. From this perspective, a qualitative approach with hermeneutic design is adopted at the methodological level, based on the interpretative paradigm, which focuses on the analysis of documentary sources focusing on three fundamental areas: the notions about teachers’ networks, the micropolitics that governs them and the characterization of their emancipatory pedagogical practices. It was found that the dialogue of knowledge, the critical analysis of educational policies, the self-reflection of practice and contexts, generate other pedagogical practices that reflect the changes at epistemic, pedagogical, axiological, social, political and educational levels that network teachers have. The above, within the development of the theoretical framework of the doctoral research Emancipatory Pedagogical Practices of the networks and collectives of teachers in Latin America, advised by Dr. Maria Cristina Martinez of the research group Education and Political Culture of the emphasis of Education, Culture and Society of the Interinstitutional Doctorate in Education of the National Pedagogical University of Colombia.